Journeys Into Night: Agewise Cinematic Constructions in Cas and Dylan and Our Souls at Night - Cristian, Réka M. (FOCUS: Papers in English Literary and Cultural Studies, 2018)
Ashton Applewhite, American writer, activist, blogger and expert on ageism, the author of This Chair Rocks: A Manifesto Against Ageism (2016), remarked in her 2017 TED (Technology, Entertainment, Design) series lecture “Let’s End Ageism” that today when the aged population is, according to the United Nations statistics, at its highest level in human history, in most societies, including developing and the developed countries alike, “people are living longer and societies are getting grayer; you read and hear about it on all media platforms and outside of them.” This essay will be about a slice of these platforms tackling cultural narratives involving longevity and ageing―and their subsequently increased visibility on the silver screen. In order to investigate ageing as a marker of life course identities in two cinematic matching and mismatching journeys into ageing, I have chosen two North American movies presented in the past five years, the Canadian-made Cas and Dylan (2013) directed by Jason Priestley and with Richard Dreyfuss and Tatiana Maslany in leading roles, and the US-produced Our Souls at Night (2017), directed by Ritesh Batra, featuring in the main roles Jane Fonda and Robert Redford. I am interested to see the ways in which the representation of senior citizens―in the above-mentioned movies all being members of the North American Baby Boomers generation―is challenging the cultural myths of aging through various acts of performativity.